6ER-003 Cost of venous thromboembolic disease in patients with lung and prostate cancer: costecat study. (March 2019) - Ana Rosa, R; Calleja, MA; Alvarado, MD; Artime, F; Bernardez, B; Escudero, V; García, C; Mangues, I; Marcos, JA
Abstract : Background: Patients with cancer are at significantly higher risk of developing, and dying from, venous thromboembolism (VTE). The CLOT and CATCH trials demonstrated the superiority of low-molecular-weight heparins (LMWH) over warfarin for recurrent VTE and established LMWH as the standard of care for cancer-associated VTE. Purpose: The aim of the present study was to determine the number of admissions and the cost of the management of VTE events occurring in patients with lung cancer (LC) or prostate cancer (PC). Material and methods: This was a multicentre, observational, ambispective pharmacoeconomic study involving six third-level hospitals. Patients with LC or PC who had suffered a first episode or a recurrent symptomatic or incidental VTE recurrence and who were receiving treatment with LMWH were included. The data was collected through medical records and/or the discharge reports, as well as the information provided by the patient during the study visit as well as the information the patient collected in their patient diary during the follow-up period. All hospitalisations and ambulatory cost related to VTE (primary diagnosis or related diagnosis) were recorded. Anticancer therapy was not collected. Costs were estimated through the consumption of resources collected in the eCRF and derivatives of the information from the patient's diaries associated with the handling of the episode of VTE. Results: Fifty-five patients were included from October 2017 to April 2018. The last patient visit was recorded in October 2018. The results will be presented during the EAHP 2019. Conclusion: Among the solid tumours with higher absolute risk of VTE are PC and LC that in our country represented the second and third most prevalent cancer according to the GLOBOCAN 2012 report. VTE represents a great economic burden on health systems and society, mainly due to the treatment of initial and recurrent events that require hospitalisation. References and/or acknowledgements: No conflict of interest.